FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PEMILIHAN PROGRAM STUDI AKUNTANSI PADA PERGURUAN TINGGI - Saepul Anwar; Ade Budi Setiawan; Kartina Fitria Ningsih (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2024)
The background of this research problem is about the selection accounting study programs which is decreasing in college university. So the aim of the research is to identify factors that influence to the decision of selecting accounting study programs at univeristy. The research method in this study uses a quantitative approach with data sources that include primary and secondary data through data collection techniques using literature studies and field research through interview mechanisms, observation, distribution of questionnaires and documentation processes